HUBUNGAN AKTIVITAS PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DENGAN KEPATUHAN DIET PADA PASIEN DIABETES MELITUS DI PUSKESMAS REJOSARI KOTA PEKANBARU TAHUN 2020: RELATIONSHIP OF PROGRAM ACTIVITIES OF CHRONIC DISEASE MANAGEMENT (PROLANIS) WITH DIET COMPLIANCE TOWARD DIABETES MELLITUS PATIENTS AT REJOSARI PUSKESMAS PEKANBARU CITY 2020 - Wilda Muchsina; Raviola Raviola; Ahmad Satria Efendi (Media Kesmas (Public Health Media), 2021)
ABSTRACT The Chronic Disease Management Program (PROLANIS) is a health care system and  proactive approach that implemented in an integrated manner involving participants, First Level Health Facilities (FKTP) and BPJS health in the framework of health care for BPJS health participants with chronic diseases to achieve optimal quality of life with effective and efficient cost service. One of  the chronic disease is Diabetes Mellitus. In Rejosari Puskesmas Pekanbaru many diabetes mellitus patients who do not follow diet activity and to find out about the implementation of PROLANI. The purpose of this study was to determine the relationship between PROLANIS activity and dietary compliance toward diabetes mellitus patients at Rejosari Puskesmas Pekanbaru in 2020. This study used quantitative with cross sectional design research. Population in this study amounted to 70 respondents of diabetes mellitus patients who visited the Rejosari Puskesmas Pekanbaru. The data obtained through univariate and bivariate method with the chi-square test (? = 0.05). Beside that, the variables in this research are medical consultation, PROLANIS group education, SMS gateway reminder, home visit, health status monitoring. The results of the bivariate analysis showed that there is a significant relationship between medical consultation (0.017 <? = 0.05), group education (? = 0.028?? = 0.05), SMS reminders (? = 0.332?? = 0.05), monitoring status (? = 0.009?? = 0.05), with dietary compliance. Based on the results, it conclusion is there are relationship between Chronic Disease Management Program Activities (PROLANIS) and Diet Compliance toward Diabetes Mellitus Patients at Rejosari Puskesmas Pekanbaru City in 2020.